(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): In the article we will answer the question as how does corporate social responsibility affect the design management process in an organization? Purpose: The purpose of this paper is to identify the characteristics and impact of socially responsible practices in design management processes in order to promote socially responsible design solutions. The aim of the paper is to examine the design management processes in the context of social responsibility. Method: A qualitative surveywill be conducted, namely,a study of foreign professional literature with an emphasis on the analysis of research written by foreign authors. We will use the following methods of research: the method of description, comparison, summation, compilation and the method of analysis. Results: Based on the study of literature and research from the subject area, we have found that social responsibility in the process of design management can be perceived as an individual or organizational dimension. Organization: The research will be useful for managers in those organizations where design is recognized as a valuable tool for achieving strategic goals and competitive advantages. The findings of the research can be considered as further recommendations for the introduction of socially responsible concepts in the design management processes, since the management of such projects requires taking into account not only the economic but also social, environmental and cultural aspects of this process. Society: The research will address the definition of factors of social responsibility in the design management processes and their impact on society as a whole. Originality: The relevance of the selected topic is reflected in the growing awareness that design is not just something beautiful and appealing, but can be a mean of improving the quality of life and living conditions. The originality of the research is mainly reflected in the focus on the process of social responsibility and its impact on the design process. Limitations / further research: The study will be confined to similar research that has already been carried out in this field. Further research could address individual factors of social responsibility in relation to design, which would complete the field research comprehensively.